EFFECTIVE COLLABORATIVE WRITING WITH GOOGLE DOCS IN EFL CLASSES - Ningsih, Putu Sri Suci (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Collaborative learning is one of the important for students to learn together and share knowledge in writing class. Also, the learning process is carried out in blended learning which technology becomes a tool to support running the learning process in the classroom. However, in EFL classes, most of the students find it difficult in writing a paper effectively. Google Docs is one of the learning platforms that can help students to collaborate in small groups to be more effective that involve all members actively doing discussions. This study aims to describe how Google Docs is an effective learning tool for students in doing collaborative writing in EFL classes. This study uses a Qualitative method using interview sessions with senior high school students. Most students find it helpful in doing collaborative writing in the classroom. This study gives a positive contribution to the teacher as innovative teaching methods.